The use of New Information and Communication Technologies as an education tool in the fight against HIV/AIDS in Fundong, Norhtwest Region, Cameroon - Lengha, Tohnain Nobert (Advances in Social Sciences Research Journal, 2016)
Fundong, a rural town found in the Northwest Region of Cameroon is located on latitude 10° 14’W and 11°15’ E, between longitudes 6° 27’ and 8° 26’N. The town enjoys the privilege of being, not just the headquarter of Boyo Division, but also of Fundong Central Sub-Division. The incidence of HIV/AIDS is critical in the area as there are several practices like the scarification of the body to apply concoctions common in the area which, may help predispose the population to HIV/AIDS infection. The affluence that characterise this small rural town favours high-risk behaviours, which expose individuals concerned to HIV/AIDS. In order to address the main objective of the study, which is the use of information and communication technologies in the fight against HIV/AIDS, data were collected at the group and household levels. At the community level, the researchers administered questionnaires and conducted focus group discussions with people of different occupational backgrounds. In the case of this study, 56% of the respondents are aware of the existence of the HIV/AIDS pandemic although constant electricity failure and the absence of radio signals in some of the localities hinder people from receiving general information, including that relating to HIV/AIDS from new information and communication channel including a rural radio station based in Fundong town. Cursory observations during fieldwork reveal that sensitisation on the HIV/AIDS pandemic have been going on in Fundong although the population still face numerous problems in an attempt to get informed and educated on this global disease- HIV/AIDS. These problems concern those related to sensitisation, the information sources, and the messages emanating from these sources as well as the problem of access to the new information and communication technologies themselves.